Equitable leadership on the ground: Converging on high-leverage practices - Galloway, Mollie K.; Ishimaru, Ann M. (Education Policy Analysis Archives, 2017)
What would leadership standards look like if developed through a lens and language of equity? We engaged with a group of 40 researchers, practitioners, and community leaders recognized as having expertise on equity in education to address this question. Using a Delphi technique, an approach designed to elicit expert feedback and measure convergence around a question of interest, these leaders participated in three rounds of data gathering. In Rounds One and Two, the 40 participants described and then rated leadership practices they believed to be most likely to mitigate race, class, and other group-based disparities between dominant and nondominant students. In Round Three, 14 of these experts participated in focus group sessions, using the findings from the first two rounds to ultimately converge around 10 high-leverage leadership practices for equity. Findings highlight the importance of leadership centered on countering systemic and structural barriers that maintain disparities, with implications for leadership preparation, policy, and tools to support organizational leadership for equity.